The balance of the carbon budget - Levin, Ingeborg (Nature, 2012)
Careful analysis reveals that the global uptake of anthropogenic carbon dioxide emissions by carbon sinks has doubled during the past 50 years — but the fractions of this absorbed by land and by sea remain unclear.